IMPLEMENTASI KURIKULUM MERDEKA DALAM KEAKTIFAN BELAJAR PESERTA DIDIK PADA SISWA MTS AL-IKHLAS TIGARAKSA TANGERANG - Nina Gantina; Ahmad Asmarudin; Nurdiansyah, Arie (Pascasarjana Universitas PTIQ Jakarta, 2025)
The Merdeka curriculum is an education system adopted in Indonesian that emphasizes freedom and creativity in the teaching and learning process, while actively learning an approach that prioritizes the active involvement of students in the learning process on Al-Quran and Hadith subjects. A Merdeka curriculum with active learning as an important aspect because it supports the curriculum objectives of creating a dynamic and responsive learning environment to the needs of students The method used in this research is a qualitative approach, namely a case study. Data collection techniques in this research used observation, interviews and documentation. Based on the research results, it can be concluded that the Merdeka curriculum has succeeded in creating a more flexible and dynamic environment, as well as encouraging students to be more actively involved in the learning process. So this can give teachers the freedom to adapt learning materials and methods according to students needs and interests, as well as encouraging the use of projectbased approaches, innovative methods and technology. This curriculum prioritizes active student participation. So that by implementing the Merdeka curriculum in students active learning at MTs Al-Ikhlas Tigaraksa there are quite significant changes.